Mobile supervised consumption services in Rural British Columbia: lessons learned - Silvina C. Mema; Gillian Frosst; Jessica Bridgeman; Hilary Drake; Corinne Dolman; Leslie Lappalainen; Trevor Corneil (BMC, 2019)
Abstract Background In 2016, a public health emergency was declared in British Columbia due to an unprecedented number of illicit drug overdose deaths. Injection drug use was implicated in approximately one third of overdose deaths. An innovative delivery model using mobile supervised consumption services (SCS) was piloted in a rural health authority in BC with the goals of preventing overdose deaths, reducing public drug use, and connecting clients to health services. Methods Two mobile SCS created from retrofitted recreational vehicles were used to serve the populations of two mid-sized cities: Kelowna and Kamloops. Service utilization was tracked, and surveys and interviews were completed to capture clients', service providers', and community stakeholders' attitudes towards the mobile SCS. Results Over 90% of surveyed clients reported positive experiences in terms of access to services and physical safety of the mobile SCS. However, hours of operation met the needs of less than half of clients. Service providers were generally dissatisfied with the size of the space on the mobile SCS, noting constraints in the ability to respond to overdose events and meaningfully engage with clients in private conversations. Additional challenges included frequent operational interruptions as well as poor temperature control inside the mobile units. Winter weather conditions resulted in cancelled shifts and disrupted services. Among community members, there was variable support of the mobile SCS. Conclusions Overall, the mobile SCS were a viable alternative to a permanent site but presented many challenges that undermined the continuity and quality of the service. A mobile site may be best suited to temporarily provide services while bridging towards a permanent location. A needs assessment should guide the stop locations, hours of operation, and scope of services provided. Finally, the importance of community engagement for successful implementation should not be overlooked.